CARP is a potential tumor suppressor in gastric carcinoma and a single-nucleotide polymorphism in CARP gene might increase the risk of gastric carcinoma. - Fang Lu; Jian-Xin Xue; Yu-Chang Hu; Lu Gan; Yi Shi; Han-Shuo Yang; Yu-Quan Wei (PLoS ONE, 2014)
BACKGROUND: The caspase-associated recruitment domain-containing protein (CARP) is expressed in almost all tissues. Recently, the tumor-suppressive function of CARP was discovered and attracted increasing attention. This study aimed to investigate the role of CARP in the carcinogenesis of human gastric carcinoma. METHODOLOGY/PRINCIPAL FINDINGS: Compared with normal gastric tissue, the downregulation of CARP expression was observed in gastric carcinoma tissue by cDNA array and tissue microarray assay. In vitro, the gastric carcinoma cell line (BGC-823) was stably transfected with pcDNA3.1B-CARP or plus CARP siRNA, and we used MTT, flow cytometry, cell migration on type I collagen, cell-matrix adhesion assay and western blot analysis to investigate the potential anti-tumor effects of CARP. The data showed that overexpressing CARP suppressed the malignancy of gastric carcinoma BGC-823 cell line, including significant increases in apoptosis, as well as obvious decreases in cell proliferation, migration, adhesion ability, and tumor growth. The tumor-suppressive effects of CARP were almost restored by siRNA-directed CARP silence. In addition, overexpression of CARP induced G1 arrest, decreased the expressions of cyclin E and CDK2, and increased the expressions of p27, p53 and p21. In vivo, the tumor-suppressive effect of CARP was also verified. A single-nucleotide polymorphism (SNP) genotype of CARP (rs2297882) was located in the Kozak sequence of the CARP gene. The reporter gene assay showed that rs2297882 TT caused an obvious downregulation of activity of CARP gene promoter in BGC-823 cells. Furthermore, the association between rs2297882 and human gastric carcinoma susceptibility was analyzed in 352 cases and 889 controls. It displayed that the TT genotype of rs2297882 in the CARP gene was associated with an increased risk of gastric carcinoma. CONCLUSIONS/SIGNIFICANCE: CARP is a potential tumor suppressor of gastric carcinoma and the rs2297882 C>T phenotype of CARP may serve as a predictor of gastric carcinoma.